2017
DOI: 10.1142/s0217984917501032
|View full text |Cite
|
Sign up to set email alerts
|

Prevision of vehicle headway effect on urban traffic with a new car-following model

Abstract: In this study, a new car-following model is established aiming to predict the variation of vehicle headways on urban road. The linear stability condition is derived corresponding to the prevision of headway in moving. The modified Korteweg–de Vries (mKdV) equation is deduced through the nonlinear analysis. The kink–antikink soliton solution of the mKdV equation can interpret the urban traffic jams near the critical point under the prevision of vehicle headway. Moreover, it is clear that the prevision of headwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In order to solve this problem, a large number of traffic models have been proposed to research the complex traffic phenomena. Such as the substantial traffic models [1][2][3][4][5][6][7][8][9][10] which mainly include car-following models [11][12][13][14][15][16][17][18][19], cellular automation models [20][21][22][23], gas kinetic models [24][25][26], and hydrodynamic lattice models [27][28][29] have been posed to study traffic flow. The optimal velocity model (for short OVM) was firstly proposed by Bando et al [30] in 1995, which has successfully revealed the dynamic evolution of traffic jam in a simple way.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve this problem, a large number of traffic models have been proposed to research the complex traffic phenomena. Such as the substantial traffic models [1][2][3][4][5][6][7][8][9][10] which mainly include car-following models [11][12][13][14][15][16][17][18][19], cellular automation models [20][21][22][23], gas kinetic models [24][25][26], and hydrodynamic lattice models [27][28][29] have been posed to study traffic flow. The optimal velocity model (for short OVM) was firstly proposed by Bando et al [30] in 1995, which has successfully revealed the dynamic evolution of traffic jam in a simple way.…”
Section: Introductionmentioning
confidence: 99%